Teologi-Etika Solidaritas dalam Diakonia Transformatif Gereja Protestan Maluku - Lewankoru, Meike Lely (Program Pascasarjana UKIM, 2024)
Maluku is still ranked as the fourth poorest province in Indonesia. The issue of poverty in Maluku is also a focus of the Maluku Protestant Church (GPM). Through the transformative diaconia program, the church continues to strive to improve the quality of life of the congregation so that they can escape the problem of poverty. This article aims to theologically analyze the ethics of solidarity in the GPM transformative diaconia program. The author uses qualitative research methods with data collection techniques in the form of in-depth interviews with GPM pastors and conducts a literature review to develop tools for analyzing the theology of solidarity ethics. The results of this research show that transformative diakonia is a GPM effort to empower the congregation to be free from the problem of poverty. The author believes that transformative diaconia, which is oriented toward human liberation from poverty is a manifestation of the theology-ethics of solidarity. The author's arguments are outlined in this research, starting from showing the reality of poverty in the Maluku community, interpreting transformative diakonia, the theological-ethical concept of solidarity, and exploring the GPM transformative diakonia service program as a form of ethical theology of solidarity.